Isbat Nikah Pasangan Suami Istri Yang Telah Meninggal Dunia Dalam Pandangan Maqashid Al-Syariah (Studi Analisis Putusan Pengadilan Agama Pekanbaru no. 0067/Pdt.P/2013/PA.Pbr) - Ridwan, Masrur; Winning Son Ashari (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2023)
The determination of marriage certificates for married couples who have not been registered with the Office of Religious Affairs (KUA) is one of the government's efforts to be able to provide guarantees of legal protection for married couples and children who will be born out of marriage, both regarding their rights and obligations as well as regarding other matters. matters relating to inheritance which can be proven by authentic evidence in the form of a marriage certificate. However, on several occasions, some circumstances were not ideal for a husband and wife, one of which was the loss of a marriage certificate and the data at the Office of Religious Affairs (KUA) were also not registered, while the husband and wife had died and the government provided a way out, namely by submitting a marriage certificate. to a religious court. With library research using a qualitative descriptive method, namely by outlining the judge's considerations in granting a request for isbat marriage, research on literature using a qualitative descriptive method, namely by describing the judge's considerations in granting a request for isbat marriage, and looking at this from the perspective of Maqashid Al-Syariah. The purpose of this research is to analyze the decision of the Pekanbaru Religious Court which discusses the marriage certificate of a husband and wife who have died by looking at the decision in Maqashid Al-Syariah. The results of this study indicate that in general the decisions issued by the Pekanbaru Religious Court are in line with Maqashid Al-Syariah namely preserving offspring (Hifzu Al-Nasl) and preserving property (Hifzu Al-Mal). Specifically, based on the considerations of the panel of judges it is also in line to legalize marriage which is the original law of isbat marriage.